Low‐voltage areas detected by high‐density electroanatomical mapping predict recurrence after ablation for paroxysmal atrial fibrillation. (8th September 2017) - Vlachos, Konstantinos; Efremidis, Michael; Letsas, Konstantinos P.; Bazoukis, George; Martin, Ruairidh; Kalafateli, Maria; Lioni, Louiza; Georgopoulos, Stamatis; Saplaouras, Athanasios; Efremidis, Theodore; Liu, Tong; Valkanas, Kosmas; et al.
Abstract: Introduction: We aimed to evaluate the extent of atrial fibrosis in paroxysmal atrial fibrillation (AF) and the correlation with ablation outcomes after pulmonary vein antral isolation (PVΑI) using a mapping system with high‐resolution and high‐spatial sampling. Methods and results: We prospectively enrolled 80 consecutive patients (45 males, median age 60.26 years) with symptomatic paroxysmal AF who were scheduled for PVAI. Prior to PVAI, high‐density bipolar voltage mapping (median number of 2, 485 points) was carried out during sinus rhythm in all patients. Criteria for an adequate left atrium (LA) shell were > 2, 000 points. Each acquired point was classified according to the peak‐to‐peak bipolar voltage electrogram based on two criteria (criterion A: healthy > 0.8 mV, border zone: 0.4–0.8 mV and scarred: < 0.4 mV, criterion Β: healthy: > 0.5 mV, border zone: 0.25–0.5 mV and scarred: < 0.25 mV). The extent of low‐voltage area < 0.4 mV significantly predicted atrial tachyarrhythmia recurrence after the blanking period (P = 0.002). In univariate analysis, the presence of LA voltage areas < 0.4 mV more than 10% of the total surface area was the only significant predictor of arrhythmia recurrence. The analysis based on window B cutoff values failed to demonstrate any predictors of arrhythmia recurrence. Conclusion: These data demonstrate that the existence of LA voltage areas < 0.4 mV more than 10% of the total LA surface area predicts arrhythmia recurrence following PVAI for paroxysmal AF.